Biomass briquettes: Raw material, technologies and densification parameters, quality and future challenges - Sanchez-Roque, Y. (2025)
The implementation of renewable energy is a viable option to reduce the use of fossil fuels and polluting emissions. Biomass is an excellent renewable energy source and is cleaner than coal. It can be obtained from organic inputs such as wood and agricultural waste and, if used sustainably, can meet the energy needs of various sectors. Densification is a technology with the potential to convert lignocellulosic waste into clean and sustainable solid biofuels. Densification involves compacting loose biomass particles using a mechanical press to produce sustainable solid biofuels with low pollutant content that are not dependent on fossil fuels. The important parameters during the manufacturing process are pressure, temperature, residence time in the press and shape of the briquettes. The production of briquettes imparts certain important properties to the briquettes, such as mechanical strength, density, combustion time and calorific quality. These properties depend on the raw material, binder and pressing process and are of utmost importance during transportation, handling and combustion of briquettes.  In accordance with the above, this paper analyzes and describes the properties of different agricultural residues used in the production of briquettes and their potential as a sustainable energy source, as well as the properties that must be evaluated to define the quality of the briquettes. One of the current and future challenges is to improve the processes for producing briquettes using residual biomass and, to the minimum extent possible, binders that favor their energy and mechanical properties.